Migration and the Demographic Shift - Anzelika Zaiceva; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2014)
This chapter connects population aging with international migration. After documenting the trends for both, we review the supply-push and demand-pull determinants of migration, focusing particularly on the role of age and aging. We subsequently discuss the literature concerning the implications of migration in the context of aging for labor markets, health and public budgets including the political economy context. Although immigration is sometimes suggested as a solution for the aging problem, the existing academic literature from different fields is more cautious about its role and potential. While large-scale selective immigration might contribute to alleviating demographic pressures, it is unlikely that immigration will increase to the unrealistically large numbers needed.
Keywords: F22; F66; J11; J14; J61; O15; 330; aging; migration; demographic pressures; elderly migration; attitudes towards migration; political economy of immigration